Overview of Mom's Knowledge About Growth and Development of Children Aged 1-5 Years at Ha Zaky Djunaid Hospital, Pekalongan - Pribadi, Wahyu Haroko; Rusmariana, Aida (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Knowledge is a result of curiosity through sensory processes, especially in the eyes and ears of certain objects. Knowledge possessed by humans has levels such as understanding (Comprehesion), application (application), analysis (analysis), synthesis (synthesis), evaluation (evaluation). The mother's role is very beneficial for the overall growth and development process of toddlers, therefore it is necessary for the mother to have proper knowledge about stimulation so that the growth and development of toddlers can be optimal. An important period in the development of children is the toddler period. Efforts to improve the quality of life of children under five are by monitoring the development of children. Objective: This study aims to describe the knowledge of mothers about the growth and development of children aged 1-5 years. Sample: The sampling technique using accidental sampling, as many as 55 respondents. Methods: This study uses a quantitative description method. For data collection using a questionnaire. Results: From 55 respondents who have children aged 1-5 years, it is known that the mother's knowledge is in the good category as many as 38 respondents (69,1%), the sufficient category is 17 respondents (30,9%), and the poor category is 0 respondents (0%). Conclusion: From the results of the research conducted, it is concluded that the knowledge of mothers about the growth and development of children aged 1-5 years in HA Zaki Djunaid Hospital has sufficient knowledge with a total of 38 respondents (69,1%).